Pulmonary metastasectomy and laser-assisted resection - Panagiotopoulos, Nikolaos; Patrini, Davide; Lawrence, David; Scarci, Marco; Mitsos, Sofoklis (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Lung is the next most common site of metastases after liver, affecting almost one third of patients with malignancies worldwide (1). Surgical removal of metastases is the second most frequent surgical intervention in thoracic surgery, representing 15–50% of the workload in European thoracic surgical centres. The most common tumors metastasizing to the lung are breast, colorectal, renal cell and head and neck carcinoma.